Measurement of forward J/ψ production cross-sections in pp collisions at s√=13 TeV - Aaij, R; Adeva, B; Adinolfi, M; Cheung, S; Evans, T; Gandini, P; Gauld, R; Greening, E; Hadavizadeh, T; Harnew, N; Hill, D; Hussain, N; et al. (Springer Berlin Heidelberg, 2015)
The production of J/ψ mesons in proton-proton collisions at a centre-of-mass energy of s√=13 TeV is studied with the LHCb detector. Cross-section measurements are performed as a function of the transverse momentum p T and the rapidity y of the J/ψ meson in the region pT< 14 GeV/c and 2.0 < y < 4.5, for both prompt J/ψ mesons and J/ψ mesons from b-hadron decays. The production cross-sections integrated over the kinematic coverage are 15.30 ± 0.03 ± 0.86 μb for prompt J/ψ and 2.34 ± 0.01 ± 0.13 μb for J/ψ from b-hadron decays, assuming zero polarization of the J/ψ meson. The first uncertainties are statistical and the second systematic. The cross-section reported for J/ψ mesons from b-hadron decays is used to extrapolate to a total bb¯¯ cross-section. The ratios of the cross-sections with respect to s√=8 TeV are also determined.